Decision Support Systems In The Acceptance Of New Administrative Staff Using The SAW Method - Hamidah Hamidah; Okkita Rizan; Delpiah Wahyuningsih (ISB Atma Luhur, 2021)
Abstract— Human resource is one very important factor in an organization or company, both public and private companies. The work success of a company is great has a major influence on the management of human resources (HR) of a company. If human resources are not good enough, it will affect the lack of good sustainability of this part of the company. Therefore, in the HR management of a company is very important, especially in accepting staff the best academic administration so that it can maximize performance. Many companies have difficulty in accepting candidates for academic administration staff accordingly to company desires. for that, a decision support system is needed that can help decision making to facilitate the acceptance of new academic administration staff. For that reason, researchers are very want to help top management in making the best decisions in recruiting new staff. This study uses the SAW (Simple Additive Weighting) method using the existing criteria determined by the company, namely administrative requirements, written tests, computer literacy, communication, and work experience. The results of the study are the value of calculating employee selection using the Simple Additive Weighting (SAW) method. to be able to help make decisions quickly, precisely, and accurately.